"If Everyone Else is Having This Talk with Their Doctor, Why Am I Not Having This Talk with Mine?": The Experiences of Sexuality and Sexual Health Education of Young Women with Spina Bifida. Issue 6 (19th April 2019) - Streur, Courtney S.; Schafer, Christine L.; Garcia, Valerie P.; Quint, Elisabeth H.; Sandberg, David E.; Wittmann, Daniela A.
ABSTRACT: Introduction: Women with spina bifida are sexually active, but most never discuss this topic with providers. Aim: To determine what women with spina bifida understand about their sexual health, how they learned about it, what questions they have, and their experiences with their sexuality. Methods: For this qualitative study, women with spina bifida ages 16 and older without marked developmental delay were individually interviewed. 25 women with spina bifida participated (mean age 27.1 years, range 16–52). Interviews were independently coded for themes by 3 reviewers, using Grounded Theory, with disagreements resolved by consensus. Main Outcome Measures: We identified overlapping themes regarding the women's perception and experience of their sexuality and sexual health education. Results: 17 of the 25 (68%) participants had been or were currently sexually active. 5 themes emerged regarding their understanding of their sexuality and their sexual experiences: (i) being perceived as asexual, (ii) sources for sex education, (iii) need for spina bifida–specific sex education, (iv) impact of spina bifida–specific features on sexual encounters, and (v) perceived relationship between low sexual self-confidence and risk for sexual assault. Clinical Implications: Women with spina bifida are sexual beings, but they are perceived as asexual by providers, which prevents them from getting adequate sexual health education and leaves them with misconceptions and unanswered questions, as well as vulnerable to sexual abuse. Strength & Limitations: The strengths of this study include the diversity of women interviewed, including their age, severity of disability, and experiences with their sexuality, as well as the ability to reach thematic saturation. The limitation of this study is that most women received treatment at a single Midwestern tertiary referral center in the United States. Conclusion: Including sexual health discussions in the usual care of women with spina bifida is critical to enhancing their sexual confidence and experience and preventing sexual abuse.